2021
DOI: 10.1126/sciadv.abf0717
|View full text |Cite
|
Sign up to set email alerts
|

The one-carbon pool controls mitochondrial energy metabolism via complex I and iron-sulfur clusters

Abstract: Induction of the one-carbon cycle is an early hallmark of mitochondrial dysfunction and cancer metabolism. Vital intermediary steps are localized to mitochondria, but it remains unclear how one-carbon availability connects to mitochondrial function. Here, we show that the one-carbon metabolite and methyl group donor S-adenosylmethionine (SAM) is pivotal for energy metabolism. A gradual decline in mitochondrial SAM (mitoSAM) causes hierarchical defects in fly and mouse, comprising loss of mitoSAM-dependent meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 75 publications
2
38
1
Order By: Relevance
“…Zhang et al have been able to elegantly demonstrate that, in addition to the SARS-CoV-2 hijacking of one-carbon metabolism, it also hijacks folate (folic acid), and that folate metabolism is absolutely critical for the transfer of one-caron units for nucleotide synthesis in addition to its important role in glutathione synthesis via the transsulfuration pathway [69]. In addition, Schober et al have demonstrated that the one-carbon pool controls mitochondrial energy metabolism via complex I and iron-sulfur clusters [70].…”
Section: Compromised Folate-mediated One-carbon Metabolism (Focm) In Lc/pasc: Importance Of Hyperhomocysteinemia (Hhcy) and Deficient Micmentioning
confidence: 99%
“…Zhang et al have been able to elegantly demonstrate that, in addition to the SARS-CoV-2 hijacking of one-carbon metabolism, it also hijacks folate (folic acid), and that folate metabolism is absolutely critical for the transfer of one-caron units for nucleotide synthesis in addition to its important role in glutathione synthesis via the transsulfuration pathway [69]. In addition, Schober et al have demonstrated that the one-carbon pool controls mitochondrial energy metabolism via complex I and iron-sulfur clusters [70].…”
Section: Compromised Folate-mediated One-carbon Metabolism (Focm) In Lc/pasc: Importance Of Hyperhomocysteinemia (Hhcy) and Deficient Micmentioning
confidence: 99%
“…More detailed STRING network analysis identified that previously established nucleotide metabolism was affected, as well as glutathione and Fe-S signalling, all of which are tightly linked to mitochondrial function. A recent study has reported that mitochondrial S-adenosylmethionine (SAM) (mitoSAM) production depends on one-carbon metabolism, and that mitoSAM depletion leads to dysregulation of ISC biosynthesis, linking nucleotide metabolism and ISC synthesis with mitochondrial function [ 63 ]. Glutathione metabolism is also related to the methionine cycle, as its product homocysteine can lead to glutathione production via the trans-sulphuration pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of SAM plays a key role in the regulation of DNA methylation, it is difficult to conclude that changes in the content of SAM can be used as all factors for changes in the degree of methylation. Schober et al [ 32 ] reported that the one-carbon metabolite and methyl group donor SAM is pivotal for energy metabolism. This further illustrates that the mechanism by which SAM affects DNA methylation changes is complex and diverse.…”
Section: Discussionmentioning
confidence: 99%